Video Games as Foreign Policy Tools: A Comparative Between Japan and Poland - Putu Radar Bahurekso; Sinta Ningrum; Dadang Enjat Munajat (Dinasti Research, 2025)
This study examines the role of video games as instruments of foreign policy by comparing Japan and Poland. Utilizing a qualitative comparative analysis, it explores how each country has strategically integrated video games into cultural diplomacy and soft power initiatives. Japan’s